Protein Misfolding, Signaling Abnormalities and Altered Fast Axonal Transport: Implications for Alzheimer and Prion Diseases - Zamponi, Emiliano; Pigino, Gustavo F. (Frontiers in Cellular Neuroscience, 2019)
Histopathological studies revealed that progressive neuropathies including Alzheimer, and Prion diseases among others, include accumulations of misfolded proteins intracellularly, extracellularly, or both. Experimental evidence suggests that among the accumulated misfolded proteins, small soluble oligomeric conformers represent the most neurotoxic species. Concomitant phenomena shared by different protein misfolding diseases includes alterations in phosphorylation-based signaling pathways synaptic dysfunction, and axonal pathology, but mechanisms linking these pathogenic features to aggregated neuropathogenic proteins remain unknown. Relevant to this issue, results from recent work revealed inhibition of fast axonal transport (AT) as a novel toxic effect elicited by oligomeric forms of amyloid beta and cellular prion protein PrPC, signature pathological proteins associated with Alzheimer and Prion diseases, respectively. Interestingly, the toxic effect of these oligomers was fully prevented by pharmacological inhibitors of casein kinase 2 (CK2), a remarkable discovery with major implications for the development of pharmacological target-driven therapeutic intervention for Alzheimer and Prion diseases.